2020
DOI: 10.1161/jaha.119.015222
|View full text |Cite
|
Sign up to set email alerts
|

Cardiospecific Overexpression of ATPGD1 (Carnosine Synthase) Increases Histidine Dipeptide Levels and Prevents Myocardial Ischemia Reperfusion Injury

Abstract: BACKGROUND Myocardial ischemia reperfusion (I/R) injury is associated with complex pathophysiological changes characterized by pH imbalance, the accumulation of lipid peroxidation products acrolein and 4‐hydroxy trans ‐2‐nonenal, and the depletion of ATP levels. Cardioprotective interventions, designed to address individual mediators of I/R injury, have shown limited efficacy. The recently identified enzyme ATPGD1 (Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 66 publications
3
41
0
Order By: Relevance
“…Our novel approach to study the role of HCDs to normal function shows that HCDs are important regulators of EC coupling in cardiac muscle, where it enhances Ca 2+ amplitude during contraction and speeds up Ca 2+ reuptake during relaxation. Our findings show that carnosine, and its methylated analogues, may have potential therapeutic roles, especially for cardiac function, expanding recent evidence indicating that increased carnosine can protect the heart against ischemia-reperfusion injury [ 41 ].…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Our novel approach to study the role of HCDs to normal function shows that HCDs are important regulators of EC coupling in cardiac muscle, where it enhances Ca 2+ amplitude during contraction and speeds up Ca 2+ reuptake during relaxation. Our findings show that carnosine, and its methylated analogues, may have potential therapeutic roles, especially for cardiac function, expanding recent evidence indicating that increased carnosine can protect the heart against ischemia-reperfusion injury [ 41 ].…”
Section: Discussionsupporting
confidence: 67%
“…This also suggests that the only clear causal link between HCDs and reduced cardiac function shown herein is impaired Ca 2+ handling. Whilst HCDs, and especially carnosine, seem to be protective under conditions of exacerbated oxidative stress [ 41 ], our data indicate that acting as an antioxidant is not a primary physiological role of HCDs in the cardiac muscle.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In our work, we found that CarnsTg mice exhibit normal cardiac function, and increasing the myocardial production of histidyl dipeptides buffers intracellular pH, facilitates glucose utilization, and attenuates cardiac injury during I/R. 18 Despite this evidence showing histidyl dipeptides imparts cardiac protection, improved glycolysis and influences numerous cellular and signaling pathways, an in-depth understanding of the histidyl dipeptide mediated effects on the genomic, proteomic and metabolomic landscape of the heart has not been performed.…”
Section: Introductionmentioning
confidence: 89%
“…Carnosine supplementation improves glucose handling [ 8 , 9 ] and renal function [ 10 ] in obese humans or mice and also increases the extrusion of advanced glycation end products (AGEs) [ 11 ]. Other studies suggest carnosine protects against ischemia-reperfusion injury in isolated mouse hearts [ 12 ] and limits atherogenesis in apolipoprotein E null(ApoE-) mice [ 13 ]. Carnosine also limits the deleterious effects of particulate matter exposure on endothelial progenitor cell function in mice [ 14 ].…”
Section: Introductionmentioning
confidence: 99%